(untitled) (Canadian Eye Care Today, 2024)
Fuchs endothelial corneal dystrophy (FECD) was first described by Ernst Fuchs in 1910. It is a bilateral corneal endothelial dystrophy characterized by progressive loss of corneal endothelial cells and formation of excrescences at the level of Descemet’s membrane called guttae. The diseased endothelium leads to corneal edema and loss of corneal clarity. FECD typically manifests in the fifth and sixth decade of life coinciding with the development of cataracts. Careful preoperative evaluation and surgical technique allows for selection of patients who can safely undergo cataract surgery alone. Some patients, however, would benefit from both cataract surgery and endothelial transplantation (EK). This can be done as a staged surgery (cataract surgery then EK or vice versa) or in combination as a single procedure. This review evaluates the management strategies for individuals with cataract and FECD to help guide surgical decision-making and planning.